(untitled) (Journal of Hama University, 2022)
The great powers, France, Britain and the United States of America, had motives and interests to move their foreign policy towards Syria, especially in 1949, which led to Syria going through a turbulent phase, and the occurrence of several military coups, moving according to the whims of the West, the first of which was the coup of Hosni al-Zaim, who showed the United States intervenetion in the coup process, and France’s role in consolidating his rule. this is evidenced by Hosni al-Zaim foreign policy, which he pursued, taking advantage of the competition between these countries. We see him signing several agreements for the peace of France and the United States, which support him. These agreements were previously rejected by the former Syrian President, Shukri al-Quwatli, which indicates the West’s incitement against him and his government. When he refused to join the Hashemite Unionist projects, which were under British auspices, the latter worked to remove him using another coup. Thus, it becomes clear to us the reality of the hidden hands, which move the internal situation in the Arab countries, in proportion to the interests of the Western powers